Sarcoidosis in adolescents - S. V. Starevskaya; M. M. Goloborod'ko; O. V. Berleva; S. V. Barashkova; M. V. Pinevskaya; V. P. Molodtsova (Туберкулез и болезни лёгких)
The child was referred for complex in-patient examination after annual fluorography screening which detected interstitial changes in the lungs, the child had been examined including biopsy of bronchi mucosa, and pulmonary sarcoidosis, stage II, was diagnosed.